An analysis of health seeking behaviour on utilizationof skilled delivery services by Maasai womenin kiekonyokie sub location of kajiado county in Kenya - Laban Lebahati Simel; Lakshmi Nanduri; Pamela A. Juma; Blasio O.Omuga (Public Health Review: International Journal of Public Health Research, 2017)
Introduction: Maternal health is one of the eight Millennium Development Goals, is central to poverty reduction and overall development,and it increased international attention for monitoring progress on maternal health and improving access to skilled attendants at deliveries. In Kenya, 44 percent of births are delivered under the supervision of a health professional, mainly a nurse or midwife. Traditional birth attendants continue to play a vital role in delivery, assisting with 28 percent of births.Objectives: This research paper aimed to analyse the role of Health Seeking Behaviour onthe utilization of skilled delivery services by Maasai women, the study population belonging to a community of nomadic life style in North of Kajiado County inKenya.Methodology: The study design was a cross sectional descriptive study adopting both quantitative and qualitative methodologies. The sample size was 264 women of reproductive age obtained by using formula given by Fisher et al., when the population is more than 10,000.The quantitative data has been analyzed using (SPSS) version 17.0 while the qualitative data was analyzed by summarizing of the themes.Results: Results show that 57.2% Maasai women go to the health facility in case of illnesses, while 7.6% consulted their mother in law., husbands make most of the decisions (40.2%) on the place of delivery of the expectant mothers whereas as the relatives make the least decisions 5.7%. Preparation of the expectant mother for delivery did not have a statistical significant p-0.046. The traditional rite of passage practices had no statistical significance p-0.190. 72% of womencould mention at least one correct danger sign for pregnancy out of the posssible four. 97.7% of the Maasai women take more than 1hour to reach to the nearest health facility and less than 1% of them take less than 30minutes to reach to the health facility , 56.1%, of the women had delivered at home while 11.4% were assisted by health personnel at the facility, 69% of those who delivered in the hospital paid > 500 shillings compared to 8% of those who paid < 500 shillings. A mount paid for skilled delivery had a statistical significance, (p<0.001).